Morphological structures of rhizophora apiculata blume. and rhizophora mucronata lam. - Shamin-Shazwan, Kamaruddin; Shahari, Rozilawati; Che Amri, Che Nurul Aini; Kassim, Zaleha; Ahmad, Zuhairi (Zibeline International Publishing, 2021)
Research on the morphological structures of R. apiculata and R. mucronata was carried out in three different regions from July to December 2018. The research aimed at observing and documenting the morphological structure of R. apiculata and R. mucronata. Samples were collected from selected locations in Peninsular Malaysia. Subsequently, samples were processed as herbarium vouchers. The vegetative and reproductive structures of both species were observed and identified. 55 morphological features were recorded and annotated as result of this research. The research revealed that vegetative and reproductive structures could differentiate R. mucronata from R. apiculata. According to this research, there were no significant differences in the morphological structures of R. apiculata and R. mucronata from three different locations. As a consequence, the data acquired in this research would be valuable for future studies on Rhizophora species.